Laser ablativo fracionado Erbium Yag no tratamento de ceratose actínica em pacientes idosos - Mattos, Alexandra Brugnera Nunes de (2021)
Photoaging is characterized by degenerative changes caused by chronic exposure to the sun, which can reduce the immune function of cells and trigger actinic keratosis (AK), which are precursors of skin cancer, especially squamous cell carcinoma (SCC). Thus, the application of Erbium YAG laser (Erb:Yag) appears as an option in the treatment of disseminated AK. The present study aimed to verify the applicability of the Erb:Yag laser in the treatment of AK and to histologically verify the impact of the laser on photoaging. This is an open, controlled, prospective and interventional clinical trial. in which 33 patients were selected who had disseminated AK in the upper limbs, one of the patient's limbs being treated with laser and the other not receiving treatment. The study was previously approved by the Research Ethics Committee of the Universidade de Passo Fundo under number 4.382.704/2020. Patients were invited to participate in the study in a private clinic and signed an informed consent form. The patients underwent clinical, photoaging (Glogau score) and histopathology evaluation through incisional biopsies of the lesions at the beginning of treatment (D0 – pre-laser) and after 30 days (D30 – post-laser). The treatment consisted of the application of a laser session, with the following parameters: ablative mode, fractional spot, 17J energy and 2 Hz velocity. Results: The study population consisted of 33 (n=33) patients, 66, 7% (n=22) aged 60-70 years and 33.3% (n=11) aged between 70-80 years. Among them, 63.6% women (n=21) and 36.4% men (n=12). Of the patients, 57.6% (n=19) had already had some type of skin cancer, among these 36.4% (n=12) had already had a diagnosis of basal cell carcinoma, 21.2% (n=7) of SCC . When performing the clinical analysis, 89.4% of patients had severe photoaging on D0, whereas on D30, 57.5% of patients had mild to moderate classification, that is, there was a 32% reduction in the aspects of skin aging (p <0.001), with a reduction in senile purpura. Regarding the histological analysis, 51.6% of the patients had moderate histological alterations on D0. In the analysis of the post-intervention group on D30, 75.7% of the patients had mild alterations at the histological level, that is, there was an important reduction in the aging aspects seen in the histology that was statistically significant (p<0.001) between pre and post intervention . The application of the Erb:Yag laser is a valid and effective modality in the treatment of AK and can be a useful method, with just one session, in preventing the development of skin cancer in patients with a history of chronic sun exposure. In addition, an improvement in the aspect of photoaging is observed, an already recognized effect of the Erb:YAG laser, which in this study also demonstrated an improvement in senile purpura. Furthermore, it is important to highlight the importance of following up on these patients for a longer time to assess the need for more sessions and the risk of recurrence.